Duas novas espécies do gênero Diospyros Dalech (Ebenaceae) da Amazônia. - Cavalcante, Paulo Bezerra (Museu Paraense Emílio Goeldi, 2011)
In this paper the author describes two new species of Diospyros (Ebenaceae) from Amazonian region. Now, the number of species of that genus extend to 35 in this region. The new spwciws D. acreana must be placed in the Section Ermellinus of Hiern in regard of the tubulous corolla and the glabrous stamens and through that, it draw near D. velutina from Brazilian Northeastern. The affinity of the another new species D. manausensis is somewhat doubtful, since the flowers are unknown, but the fruit is like that of D. guianensis.